Dinamika Perencanaan Tata Guna Lahan di Kabupaten Kediri - Putri, Ninda Adisti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The imbalance between the needs with sufficient land, meanwhile, needs to be compared with land requirements. Kediri Regency has the potential for rapid development. This is a challenge to the existing land use planning policy in Kediri Regency. This study aims to predict the dynamics of land use change in Kediri Regency until 2030. The prediction model was built using the Cellular Automata approach based on an analysis of land use change trends from 2009 to 2018 taking into account the weight of the driving factors obtained using the AHP method. The results of modeling validation show an accuracy rate of 96.26%. The result is that in 2030 there will be a significant increase in the use of industrial land and warehousing of 331.56 Ha and settlements of 3650.94 Ha in Kediri Regency. But there are still mismatches between the dynamics of the regional spatial plan to be a challenge going forward in order to achieve the goals of the expected development. Modeling using Cellular Automata can be applied as an alternative to new methods in spatial policy evaluation.